"Y Sign" at the Level of the 3‐Vessel and Trachea View: An Effective Fetal Marker of Aortic Dextroposition Anomalies in the First Trimester. (27th December 2017) - Pasternok, Marcin; Nocun, Agnieszka; Knafel, Anna; Grzesiak, Mariusz; Orzechowski, Maciej; Konarska, Katarzyna; Ludwin, Artur; Ludwin, Inga; Zymroz, Piotr; Parzynska, Anna; Wiechec, Marcin
Abstract : Objectives: The "Y sign" at the level of the 3‐vessel and trachea view corresponds to thinning of main pulmonary artery and arterial duct and a dilated transverse aortic arch. The purpose of this study was to evaluate the Y sign for the diagnosis of aortic dextroposition anomalies at the time of the first‐trimester scan and to assess the screening performance of only the Y sign, only abnormal left axis deviation (axis sign), and their combination for the diagnosis of aortic dextroposition anomalies. Methods: A prospective evaluation of 6025 pregnant women undergoing first‐trimester ultrasonography was conducted. The cardiac axis was measured in all examined patients and considered abnormal (positive axis sign) at greater than 57 °. The frequency of the Y sign and the axis sign was assessed for this population, and their screening performance for the diagnosis of aortic dextroposition anomalies was calculated. Results: A total of 5775 patients fulfilled the inclusion criteria. Aortic dextroposition anomalies were diagnosed in 17 cases (tetralogy of Fallot in 8 and Fallot‐like double‐outlet right ventricle in 9). The Y sign was found in 18 of 5775 (0.3%) fetuses examined, of which 7 of 18 were confirmed with tetralogy of Fallot, 9 of 18 with a Fallot‐like double‐outlet right ventricle, and 2 of 18 with pulmonary stenosis. A positive axis sign of greater than 57 ° was found in 20 fetuses, including 4 with normal heart anatomy. The sensitivity values of the Y sign, the axis sign, and their combination were 94%, 76%, and 94%, respectively. Conclusions: Visualization of the Y sign should increase the suspicion of aortic dextroposition anomalies in the late first trimester. The screening performance of the Y sign alone and in combination with an abnormal cardiac axis was high and may aid in the early diagnosis of aortic dextroposition anomalies in the fetus.